THE EFFECT OF COMMUNICATION ON EMPLOYEE PERFORMANCE AT CENTER OFFICE OF HASANUDDIN UNIVERSITY WITH MOTIVATION AS INTERVENING VARIABLES - Herlina Irad; Mahlia Muis; Wahda Rasjid (Hasanuddin Journal of Applied Business and Entrepreneurship, 2020)
National education institutions should be able to compete in this globalization era. This study aims to determine the effect of communication on performance with motivation as an intervening variable at the Center Office of Hasanuddin University. This research is a quantitative descriptive using primary data in the form of a questionnaire. The population in this study were 214, of the population taken by using the Slovin technique of 139 people with random sampling. Data were analyzed using path analysis with SPSS version 25. Structural equation test results show that all variables have a positive or direct effect because all beta values ​​are positive. The results of partial testing (T-test) showed that all the variables had a significant effect because all variables had t-counts greater than t-table. Simultaneous test results (F test) found that communication, motivation, and discipline simultaneously influence (simultaneously) on employee performance because the value of F-count is greater than F-table. The conclusion from this study is that the variables of communication and motivation have a positive and significant effect on employee performance.